PERDAGANGAN ILEGAL KUKANG (Nycticebus spp.) DI JAWA BARAT BERDASARKAN INFORMASI MEDIA SOSIAL 2019-2020 - Putri, Amelya Apriliani; Rusli, Abdul Rahman; Sasongko, Dwi Agus (Jurnal Nusa Sylva, 2021)
Slow lorises in the one of Indonesia's protected primates. Slow lorises are nocturnal (active at night) animals that move very slowly with a variety of habitat types. Slow lorises are also the second most popular primate animal as a pet. The high level of illegal slow loris trade in Indonesia is thought to be due to low knowledge and awareness of the community and driven by economic factors due to the high interest in traded animals. This study aims to obtain data on the types, conditions or body parts of slow lorises traded and to map the hotspots for illegal online slow loris trade in the West Java. Testing data on the illegal online slow loris trade uses primary and secondary data. Data on the online illegal trade in slow lorises was obtained through social media observations, data analysis is carried out in quantitative and qualitative descriptive methods. The results of this study show that lorises in a dead (dead) condition are more common, and the hotspots for the illegal trade of slow lorises in the West Java region through social media are Ciamis, Pangandaran, Indramayu, Kuningan, Tasikmalaya, Depok, Bandung, and BogorÂ Â